Aspects of social behavior in Poecilia latipinna (Lesueur) - Baird, Ronald C. (1973)
Agressíve and courtship behavioral patterns are prominent in the repertoire of Poecilia latipinna, a small poeciliid fish of shallow subtropical North American coastal waters. Courtship involves a characteristic set of behavioral patterns in which the male plays a dorninant role; the species is sexually dimorphic, and rnorphological differences play important roles in courtship. Aggressive behavior has been observed in both sexes, and has been linked to both feeding and courtship. Size and sex are important in dorninance determination, and in confined areas, especially at low popuIation densities, stable hierarchies are formed. The role of aggressive behavior in the social structuring or organization of populations is discussed, as well as sorne differences between certain freshwater and marine populations.